Effects of UV-Vis Irradiation on Vanadium Etioporphyrins Extracted from Crude Oil and the Role of Nanostructured Titania - Debra Jene Kirkconnell Reyes; Andrés García Saravia Ortiz de Montellano; Rudy Amilcar Trejo Tzab; Gerko Oskam; Juan José Alvarado Gil (International Journal of Photoenergy)
The role of UV-irradiation on oil and its derivatives is particularly important for analyzing the degradability of specific oil compounds. Also, nanostructured-TiO2 is one of the most promising photocatalysts so it is expected to be useful in their degradation. However the complexity of crude oil, as well as that of the reactions involved, is such that the effect of the presence of TiO2 under illumination is not well understood. In this paper, the influence of UV-Vis irradiation on vanadium etioporphyrins, extracted from crude oil from Dos Bocas, Tabasco, Mexico, is studied using UV-Vis spectrophotometry in the absence and presence of nanostructured TiO2 or nitrogen-doped TiO2 modified with copper (N-TiO2/Cu). It is shown that the addition of water shortens the time to start photodegradation. However, once this process has initiated, the system enters a second stage, that is very similar for samples with or without water. It is also shown that the use of N-TiO2/Cu induces an important delay in the initiation of the porphyrins’ photodegradation process. Additionally, it has been found that the presence of TiO2 in samples extracted with water induces a small reduction in the photodegradation duration and, hence, that TiO2 can catalyze the degradation of petroporphyrins.